(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. Anxiety, preoccupation, immaturity, and self-absorption prevent us from empathizing with other people. During two years the sufficient amount of students and teachers of medical college were analyzed, to do an encouraging conclusion that a level of empathy is at low level. Does a medical worker need to be a person with a high level of empathy or will this human quality only interfere with his professional duty? The important point is about that we must always remember the basis of medical humanism is the universal human moral standards, clearly formulated by medical ethics and medical deontology. One of such norms is responsive attitude toward pain, suffering and illness of another person.